PENERAPAN MODEL COGNITIVE ACADEMIC LANGUAGE LEARNING APPROACH (CALLA) DALAM PEMBELAJARAN CHOUKAI DI STBA JIA - Jeniar Noverisa , Eva (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2019)
This research objective is to examine the results of CALLA model application in learning Choukai. The use of the model is expected to help learners maximize their learning proses and results. Subjects of this study are 28 students that divided into two groups which it consists of 14 students for each. The experimental group is treated by implementing CALLA model to improve listening comprehension for five weeks, whereas the control group is treated without any particular ways during class. The results showed that the CALLA group has gained 82.28 point's averages score, it is better than non-CALLA group that gained 71.92 point. The t-test result showed that there is a significant difference of students listening comprehension competence between CALLA group and non-CALLA group. The questionnaire result showed that students liked to use this model since it can help and facilitate them to comprehend the topic of listening text better. Furthermore, it helps them improving their motivation in learning Japanese.